An Initial Exploration of the Implementation of a Discussion-Based Course Design for the Higher Vocational Course “Music Fundamentals” Based on the ADDIE Model—Aiming at the Cultivation of Core Professional Competencies - Zhang, Chi; Cui, Xiangzhe (Journal of Educational Research and Policies, 2025)
As an art teaching course that integrates musical literacy and comprehensive practice, “Music Fundamentals” has always been recognized and valued in normal education. However, due to its strong theoretical nature, it has been taught and practiced as a pure theory course in talent training and teaching plans. In order to cultivate the core professional competencies of students majoring in normal education in vocational colleges in the new era and to provide experience for the design and reform of this course, this paper systematically analyzes the aimportant links and elements of course design based on the ADDIE teaching model, clarifies teaching objectives, selects appropriate teaching methods and means to highlight the characteristics of normality, practice, and professional features, adjusts the course teaching structure, and enables students to support graduation requirements and training objectives through the course study, ultimately improving the quality of talent training in English education.